Transcriptional Regulation of Stearoyl-Acyl Carrier Protein Desaturase Genes in Response to Abiotic Stresses Leads to Changes in the Unsaturated Fatty Acids Composition of Olive Mesocarp - Hernández, M. Luisa; Sicardo, M. Dolores; Alfonso, Miguel; Martínez-Rivas, José M. (Frontiers in Plant Science, 2019)
In higher plants, the stearoyl-acyl carrier protein desaturase (SAD) catalyzes the first desaturation step leading to oleic acid, which can be further desaturated to linoleic and α-linolenic acids. Therefore, SAD plays an essential role in determining the overall content of unsaturated fatty acids. We have investigated how SAD genes expression and unsaturated fatty acid composition are regulated in olive (Olea europaea) mesocarp tissue from Picual and Arbequina cultivars in response to different abiotic stresses. The results showed that olive SAD genes are transcriptionally regulated by temperature, darkness and wounding. The increase in SAD genes expression levels observed in Picual mesocarp exposed to low temperature brought about a modification in the unsaturated fatty acids content of microsomal membrane lipids. In addition, darkness caused the down-regulation of SAD genes transcripts, together with a decrease in the unsaturated fatty acids content of chloroplast lipids. The differential role of olive SAD genes in the wounding response was also demonstrated. These data point out that different environmental stresses can modify the unsaturated fatty acid composition of olive mesocarp through the transcriptional regulation of SAD genes, affecting olive oil quality.